1992
DOI: 10.1111/j.1365-2273.1992.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Underlay tympanoplasty with the graft lateral to the malleus handle

Abstract: In conventional underlay tympanoplasty the graft is placed medial to the malleus handle. The present study evaluates the results of a modification of this technique, in which the graft is placed lateral to the malleus handle, which has been dissected from the drum remnants. 39 ears with predominantly large or anterior pars tensa perforations were operated upon in this manner. After a median observation time of 20 months one ear was found to have a small reperforation. All ears had normal tympanomeatal angles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
24
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 7 publications
4
24
0
1
Order By: Relevance
“…16 Sckolnick et al reported a poor success rate for chronic ear perforation. 4 A similar success rate (90 per cent) was achieved by Kartush et al in a series of 120 patients who underwent over-underlay tympanoplasty. No patient had vertigo or facial nerve palsy; decreased hearing and a history of ear discharge were the main presenting complaints.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…16 Sckolnick et al reported a poor success rate for chronic ear perforation. 4 A similar success rate (90 per cent) was achieved by Kartush et al in a series of 120 patients who underwent over-underlay tympanoplasty. No patient had vertigo or facial nerve palsy; decreased hearing and a history of ear discharge were the main presenting complaints.…”
Section: Discussionsupporting
confidence: 60%
“…[16][17][18][19] This study analysed the influence of age and illness duration on tympanoplasty success rate. 21 The aim of developing the modified over-underlay tympanoplasty technique (combining the underlay 4,6 In our patients, the tympanomeatal flap was elevated as described by Yung and fresh temporalis fascia was used for grafting. Similarly, Vartiainen and Nuutinen reported that age distribution did not influence the success rate in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, several surgical techniques have been tried to improve the take-up rate and hearing results such as underlay, overlay, cartilage tympanoplasty, [5] Anterior tucking [anterior hitch], [8] over-under technique, [9,10] vein graft, [2] mediolateral tympanoplasty, [11] sandwich graft tympanoplasty, [12] modified window shade by Schraff et al, [13] paper patching, lobule fat graft, etc. We are presenting a modification of over-under tympanoplasty using a pedicle temporalis fascia graft to improve the graft take-up rate without jeopardising the hearing results.…”
Section: Discussionmentioning
confidence: 99%
“…[9] And hearing improvement varies from 70% [11] to 85.7%. [15] Nardone M et al reported 78% success rate in a critical analysis of long-term results in a 1,000-adult patient series.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior canal ''blunting'' and lateralization of the graft (20) can occur, particularly with onlay or lateral techniques (discussed later). Anterior canal ''blunting'' and lateralization of the graft (20) can occur, particularly with onlay or lateral techniques (discussed later).…”
mentioning
confidence: 99%